2016
DOI: 10.1021/acs.energyfuels.6b00450
|View full text |Cite
|
Sign up to set email alerts
|

Migration and Emission Characteristics of Trace Elements in a 660 MW Coal-Fired Power Plant of China

Abstract: 11Trace elements (TEs) emitted from coal-fired power plant has caused widespread 12 concern. The onsite investigation of the TEs emission from a Chinese 660MW 13 pulverized coal (PC) boiler equipped with SCR, ESP, WFGD and WESP was 14 conducted by using US EPA Method 29. Simultaneous sampling of the coal, bottom 15 ash, ESP ash, flue gas and by-products from WFGD and WESP process was 16 performed. Results show that TEs mass balance rates for the entire system, furnace 17 and each air pollution control device (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 27 publications
1
30
0
Order By: Relevance
“…It has been confirmed that CFA conducts as a carrier of hazardous trace elements (HTEs) [133,134]. Although fabric filter or electrostatic precipitator had been widely equipped in smokestacks of power plants, PM with various assemblies of HTEs caused by CFA releasing still resulted in high risk on atmospheric environment and human health [135][136][137][138][139]. Dwivedi et al [140] found that oxidative DNA damage in human cells was attributed to nanoscale CFA.…”
Section: Discussion On Potential Health Risks Of Enriched Ga and In Imentioning
confidence: 99%
“…It has been confirmed that CFA conducts as a carrier of hazardous trace elements (HTEs) [133,134]. Although fabric filter or electrostatic precipitator had been widely equipped in smokestacks of power plants, PM with various assemblies of HTEs caused by CFA releasing still resulted in high risk on atmospheric environment and human health [135][136][137][138][139]. Dwivedi et al [140] found that oxidative DNA damage in human cells was attributed to nanoscale CFA.…”
Section: Discussion On Potential Health Risks Of Enriched Ga and In Imentioning
confidence: 99%
“…Here the ratios are in the range of 80.0%~114.2%, and the relative deviations of the mass balance are in the range of 6.2%~8.1%. Because of the slight variation of boiler operating conditions, the fluctuation of components in solid and liquid samples and the complexity and uncertainty in sampling and analysis process, values in the range of 70%~130% are acceptable [42][43][44]. An analysis of these data suggests the current study can be considered reliable and satisfactory.…”
Section: Mass Balance Ratio Of As In the Entire Systemmentioning
confidence: 80%
“…According to the coal properties and ash compositions, the acid dew point of the flue gas can be estimated using thermodynamic method, which is given as follows: fh ar ,zs 3 ar,zs…”
Section: Flue Gas Acid Dew Pointmentioning
confidence: 99%
“…With the improvement of ecological environment awareness, the impacts of pollutant emission from coal-fired power plants on frequent haze weather have gradually attracted attention [1,2]. Currently, China has fully carried out strict ultra-low emission standard for coal-fired power plants, which specifies particulate matter (PM), sulfur dioxide (SO 2 ) and nitrogen oxides (NO x ) shall not exceed 5, 35 and 50 mg/Nm 3 [3]. Correspondingly, the technologies that achieve the ultra-low emission target through a series of processes or devices are called ultra-low emission technologies.…”
Section: Introductionmentioning
confidence: 99%